Settlement, landscape and identity in medieval royal forests: the Impact of forest law on Sherwood and the Peak, c. AD 650 to 1348 - Dicken, Craig Arthur (2018)
This research looks to present a reinterpretation of medieval forests, the least well understood landscapes of medieval Western Europe. The thesis focuses on the Forest of High Peak and Sherwood Forest and seeks to address several key themes, including the diversity of forest landscapes, the long-term impact of Forest Law, and evidence for power-relations and social dynamics within the forests. A wide variety of sources are utilised within this research, including map analysis and regression techniques, analysis of material culture, documentary sources, place names, church architecture, and funerary monuments.